2014
DOI: 10.1002/elps.201300502
|View full text |Cite
|
Sign up to set email alerts
|

Rapid screening of the heterogeneity of DNA methylation by single‐strand conformation polymorphism and CELIF in the presence of electro‐osmotic flow

Abstract: DNA methylation is a complex event in epigenetic studies because of both the large CpG islands present upstream of the promoter region and the different distribution of DNA methylation despite similar methylation levels. For this reason, we proposed a fast, cost-effective method for the screening of DNA methylation based on SSCP and CE-LIF. In this study, the PCR products that were amplified from bisulfite-treated genomic DNA were denatured at 94°C, followed by immediate chilling in ice water to form the ssDNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Chen and Chang et al 69 reported the combination of COBRA and electrophoresis with laserinduced fluorescence for determining the heterogeneity of DNA methylation. Chang's group further reported 70 a Fig. 4 (A) Sample pre-processing module for on-chip DNA bisulfite conversion consisting of a microchamber, 3D micromixer, and microchannel.…”
Section: Bisulfite-based Methylcytosine Assaymentioning
confidence: 99%
“…Chen and Chang et al 69 reported the combination of COBRA and electrophoresis with laserinduced fluorescence for determining the heterogeneity of DNA methylation. Chang's group further reported 70 a Fig. 4 (A) Sample pre-processing module for on-chip DNA bisulfite conversion consisting of a microchamber, 3D micromixer, and microchannel.…”
Section: Bisulfite-based Methylcytosine Assaymentioning
confidence: 99%
“…CpG sites are converted to TpG sites and mCpG (5‐methyl cytosine and guanine dinucleotide) sites are converted to CpG sites in the resultant PCR amplicons. These base changes can be detected by several methods, such as hybridization‐based techniques , electrophoretic sorting , pyrosequencing , gold/DNA affinity‐based techniques , and single‐base extension (SBE) assays.…”
Section: Introductionmentioning
confidence: 99%
“…DNA polymerase incorporates a single dideoxynucleotide triphosphate (ddNTP) that is complementary to the target base. Single base‐extended primer (i.e., SBE product) can be detected by various methods, including CE , MALDI‐TOF MS , surface enhanced Raman spectroscopy , and BeadChip array . However, all of these techniques are expensive, use high‐precision instruments, and require time‐consuming separation or cleanup/concentration of the SBE products.…”
Section: Introductionmentioning
confidence: 99%